Salvage Radiosurgery After Subtotal Resection for Catecholamine-secreting Jugular Paragangliomas: Report of Two Cases and Review of the Literature. Issue 1 (January 2019) - Chweya, Cynthia M.; Patel, Neil S.; Young, William F.; Pollock, Bruce E.; Link, Michael J.; Carlson, Matthew L.
Abstract : Objectives: Catecholamine-secreting jugular paragangliomas (JPs) represent a rare subset of head and neck paragangliomas that may present with hypertension, arrhythmia, or syncopal episodes. Subtotal resection to protect critical neurovascular structures may result in persistent catecholamine excess from residual tumor. Herein, we report our experience with stereotactic radiosurgery (SRS) for salvage treatment of catecholamine-secreting JP following subtotal microsurgical resection. Patients: Adult patients treated with SRS after subtotal microsurgical resection of catecholamine-secreting JP. Interventions: SRS. Main Outcome Measures: Post-treatment catecholamine and metanephrine levels, clinical outcomes, and tumor control. Results: Of 85 patients with JPs treated with primary or salvage radiosurgery between 1990 and 2017, 2 (2%) harbored nonmalignant secreting tumors. Patient 1 developed catecholamine excess with elevated norepinephrine (NE) at 475 mcg/24 hours (normal < 80 mcg/24 h). Following subtotal resection, she developed catecholamine excess with radiographic evidence of tumor growth and therefore underwent SRS. Three years post-SRS and beyond, catecholamine levels remained normalized (NE 62 mcg/24 h at 10 yr) and tumor volume remained stable on serial MRI studies over the 17-year follow-up period. Patient 2 developed symptomatic arrhythmia and was found to have a JP. Urine norepinephrine (NE) was elevated at 213 mcg/24 hours. She underwent nerve-sparing subtotal resection and upfront SRS was used to treat residual tumor. Twenty months following SRS, the area of residual JP had not enlarged in size and catecholamine levels remained normal (NE 46 mcg/24 h). Conclusions: Radiosurgery can be used in salvage treatment of catecholamine-secreting JP, providing durable tumor control and resolution of catecholamine excess. For patients with large catecholamine-secreting JP and normal lower cranial nerve function, aggressive nerve-sparing subtotal resection with adjuvant radiosurgery may offer a low-morbidity alternative to gross total resection. Further study of this subset of patients is warranted to substantiate these promising, yet preliminary findings.